Research on medication use in the neonatal intensive care unit. Issue 4 (3rd April 2019) - Allegaert, Karel; Simons, Sinno; Van Den Anker, John
ABSTRACT: Introduction : Research on medication use aims at assessing how much of current pharmacotherapy is rational. In neonates, this is hampered by extensive off-label drug use and limited knowledge. Areas covered : We report on medication use research and have conducted a systematic review of observational studies on medication use to provide an updated overview on characteristics, objectives, methods, and patterns in hospitalized neonates. Moreover, a review on aspects of medication use for opioids, anti-epileptics, gastric acid-related disorders and respiratory stimulants with emphasis on trends and impact of interventions is presented, illustrating how research on medication use can contribute to improved neonatal pharmacotherapy and more focused research. Medication use reports describe patterns and provide signals on irrational use, benchmarking, or can guide research priorities. Moreover, this may generate information on how neonatal health topics and their pharmacotherapy are handled over time or across regions. Expert opinion : Research on medicine utilization is relevant, since it will inform us on aspects like trends, variability, or about the impact and pattern of implementation of guidelines in neonates. Further progress necessitates to merge datasets on medication use with clinical characteristics, and perinatal drug use remains an area in need of additional research.